2009
DOI: 10.1111/j.1528-1167.2009.02160.x
|View full text |Cite
|
Sign up to set email alerts
|

Rufinamide for the adjunctive treatment of partial seizures in adults and adolescents: A randomized placebo‐controlled trial

Abstract: SUMMARYPurpose: To evaluate efficacy and safety of adjunctive treatment with rufinamide 1600 mg twice daily in subjects aged ‡16 years with refractory partial seizures. Methods: This double-blind, placebo-controlled, randomized, parallel-group, multicenter trial included an 8-week baseline phase and a 13-week double-blind phase. Treatment was initiated with rufinamide 400 mg twice daily or placebo; rufinamide was titrated to 1600 mg twice daily. Percentage change in partial seizure frequency was the primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(143 citation statements)
references
References 17 publications
6
125
0
12
Order By: Relevance
“…В обзоре G. Coppola (2011) указывается, что пер-воначально эффективность и безопасность руфина-мида были доказаны в 3 рандомизированных контро-лируемых исследованиях: в дополнительной терапии фокальных приступов у взрослых и подростков (Brodie M. J. и соавт., 2009; Palhagen S. и соавт., 2001) и в ле-чении генерализованных приступов, ассоциирован-ных с СЛГ (Glauser T. и соавт., 2008) [13,15,16,29].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
See 1 more Smart Citation
“…В обзоре G. Coppola (2011) указывается, что пер-воначально эффективность и безопасность руфина-мида были доказаны в 3 рандомизированных контро-лируемых исследованиях: в дополнительной терапии фокальных приступов у взрослых и подростков (Brodie M. J. и соавт., 2009; Palhagen S. и соавт., 2001) и в ле-чении генерализованных приступов, ассоциирован-ных с СЛГ (Glauser T. и соавт., 2008) [13,15,16,29].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
“…Умень-шение частоты приступов более чем на 50 % наблюда-ли у 28,2 % пациентов в группе руфинамида и у 18,6 % -в группе плацебо (p = 0,04). Отмечена хорошая переносимость руфинамида (наиболее рас-пространенные побочные эффекты включали голово-кружение, тошноту, диплопию и атаксию; наблюда-лись преимущественно в фазу титрации) [13].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
“…Clinical trials showed modest efficacy in partial seizures in adults, and it is not approved for use in partial seizures at the present time. The most common adverse events associated with rufinamide are somnolence, dizziness, nausea, diplopia, and ataxia [83,84]. It is contraindicated for use in patients with the Short QT syndrome.…”
Section: Indications Usage and Potential Side Effectsmentioning
confidence: 99%
“…In a published trial of rufinamide in partial seizures, rufinamide was associated with a 20.4% median reduction in seizure frequency compared to a 1.6% increase in the placebo arm (p = 0.02) [84].…”
Section: Efficacymentioning
confidence: 99%
“…Nur 3 von 31 Patienten beklagten Nebenerscheinungen in Form einer Tagesmüdig-keit. Diese wird in der Produktinformation als sehr häufige Nebenwirkung (Häu-figkeit ≥1:10; [4]) angegeben und auch in allen anderen Studien als die häufigs-te beschriebene Nebenwirkung berichtet [3,8,9]. Bei 3 Patienten, alle mit einer schweren frühkindlichen Hirnschä-digung, wurde hingegen eine Verbesserung der Vigilanz berichtet.…”
Section: Diskussionunclassified